Direct arterial injection of hyperpolarized 13C‐labeled substrates into rat tumors for rapid MR detection of metabolism with minimal substrate dilution. Issue 6 (12th February 2017) - Reynolds, Steven; Metcalf, Stephen; Cochrane, Edward J.; Collins, Rebecca C.; Jones, Simon; Paley, Martyn N.J.; Tozer, Gillian M.
Abstract : Purpose: A rat model was developed to enable direct administration of hyperpolarized 13 C‐labeled molecules into a tumor‐supplying artery for magnetic resonance spectroscopy (MRS) studies of tumor metabolism. Methods: Rat P22 sarcomas were implanted into the right inguinal fat pad of BDIX rats such that the developing tumors received their principle blood supply directly from the right superior epigastric artery. Hyperpolarized 13 C‐molecules were either infused directly to the tumor through the epigastric artery or systemically through the contralateral femoral vein. Spectroscopic data were obtained on a 7 Tesla preclinical scanner. Results: Intra‐arterial infusion of hyperpolarized 13 C‐pyruvate increased the pyruvate tumor signal by a factor of 4.6, compared with intravenous infusion, despite an approximately 7 times smaller total dose to the rat. Hyperpolarized glucose signal was detected at near‐physiological systemic blood concentration. Pyruvate to lactate but not glucose to lactate metabolism was detected in the tumor. Hyperpolarized 13 C‐labeled combretastatin A1 diphosphate, a tumor vascular disrupting agent, showed an in vivo signal in the tumor. Conclusions: The model maximizes tumor substrate/drug delivery and minimizes T1 relaxation signal losses in addition to systemic toxicity. Therefore, it permits metabolic studies of hyperpolarized substrates with relatively short T1 and opens up the possibility for preclinical studies of hyperpolarized drug molecules. Magn Reson Med 78:2116–2126, 2017. © 2017 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.